Standard precautions: knowledge and practice of clinical students at the College of Medicine, University of Ibadan - Olawuyi, Dimeji Abdulsobur; Ibekwe, Jonas Paul; Jerry-Ogeme, Oghenemaro Akpooghene; Ibrahim, Aisha; Ehiorobo, Osaretin Vanessa; Dada, Victoria Oluwamayokun; Asogwa, Emmanuella Chinenye; Akinkuebi, Oluwayomi Victoria; Ayooluwa, Ogunleye Moyinoluwa; Amakom, Nneka Lilian; et al. (International Journal of Infection Control, 2026)
Background: Hospital-acquired infections are a significant cause of morbidity and mortality in healthcare settings among patients and healthcare workers, including clinical students. The frequent exposure of students during their clinical postings to various sources of infections emphasizes the need for adherence to standard precautions (SP). This study aimed to assess the knowledge and practice of SP among the clinical students of the College of Medicine, University of Ibadan, Nigeria. Methods: A descriptive cross-sectional study was conducted. Data on sociodemographic, domains of SP knowledge and practice, and source of students’ knowledge were collected via a self-administered online questionnaire. Categorical variables were compared using Chi-square and Z tests, while numerical data were analyzed with Mann–Whitney and Kruskal–Wallis tests. Logistic regression identified predictors of the assessed SP knowledge and practice domains. SPSS v20 was used for data analysis, and P < 0.05 was used as the statistical significance level. Results: Among 371 clinical students, 55.8% were MBBS students, 78.7% were Christians, and 80.6% were aged 21–25 years. Participants’ overall knowledge score was average, and 131 (36.1%) students scored ≥ 29 (out of 36 points) which was considered an acceptable level of knowledge. The overall practice score was average with a mean practice score of 11.76 (± 2.50) out of 17. Participants’ main sources of knowledge were self-learning and the school curriculum. Logistic regression revealed that participants’ knowledge correlated with gender, year of study, and prior knowledge, while practice correlated with age and department. Conclusion: The students’ average knowledge and practice and significant reliance on self-learning of SP is alarming. We recommend that universities and medical colleges integrate early and continuous SP education and training into medical curriculum.